The anatomy of human rights in Israel : constitutional rhetoric and state practice / Assaf Meydani. - Meydani, Assaf (Cambridge University Press, 2014)
Why is there such a large gap between the declarations that countries make about human rights and their imperfect implementation of them? Why do states that have enacted laws and signed treaties about human rights choose to not enforce these laws in daily life? Why have activists failed to achieve the goals of ensuring human rights domestically and internationally? This book examines the issue of human rights in the Israeli domestic arena by analyzing the politics and strategies of defending human rights. To do so, it integrates the tools of social choice theory with a unique institutionalist perspective that looks at both formal and informal, and local and international factors. The book offers an analysis explaining the processes through which Israel is struggling to promote human rights within a specific institutional environment, thus determining the future of Israeli democracy and its attitude toward human rights.